Highly Enantioselective Michael Addition of α-Substituted Nitrophosphonates to a Vinyl Sulfone - Chen, Guo-Ying; Lu, Yixin (Synthesis, 2013)
Organocatalytic asymmetric Michael reaction of α-substituted nitrophosphonates to phenyl vinyl sulfone catalyzed by cinchona alkaloid-derived tertiary amine-thioureas afforded α,α-disubstituted nitrophosphonates in very good yields and excellent enantiomeric excesses.
Keywords: thiourea; Michael Addition; cinchona alkaloid; vinyl sulfone; nitrophosphonate